High-flexibility combinatorial peptide synthesis with laser-based transfer of monomers in solid matrix material - Löffler, Felix; Förtsch, Tobias; Popov, Roman; Mattes, Daniela; Schlageter, Martin; Ridder, Barbara; Bojničić-Kninski, Clemens von; Weber, Laura; Bykovskaya, Valentina; Meier, Michael A. R.; Bräse, Stefan; Powell, Annie K.; et al. (Nature Communications, 2016)
Laser writing is used to structure surfaces in many different ways in materials and life sciences. However, combinatorial patterning applications are still limited. Here we present a method for cost-efficient combinatorial synthesis of very-high-density peptide arrays with natural and synthetic monomers. A laser automatically transfers nanometre-thin solid material spots from different donor slides to an acceptor. Each donor bears a thin polymer film, embedding one type of monomer. Coupling occurs in a separate heating step, where the matrix becomes viscous and building blocks diffuse and couple to the acceptor surface. Furthermore, we can consecutively deposit two material layers of activation reagents and amino acids. Subsequent heat-induced mixing facilitates an in situ activation and coupling of the monomers. This allows us to incorporate building blocks with click chemistry compatibility or a large variety of commercially available non-activated, for example, posttranslationally modified building blocks into the array’s peptides with >17,000 spots per cm2.